O movimento do carvoejamento na Amazônia oriental brasileira: a dinâmica da produção do carvão vegetal em Rondon do Pará - Mayka Danielle Brito Amaral (Confins)
The article aims to analyze the dynamics of charcoal in the eastern Amazon, specifically in Rondon do Pará, located in the southeast of Pará State. Therefore we used as a methodology secondary sources, of the Brazilian Institute of Geography and Statistics (IBGE) and of the State Department of Environment (SEMA), as well as the analysis of primary sources obtained through field work in bunkers and on private properties located within the rural settlements bunkers and camps of land reform in this municipality. These procedures revealed the fragility of government agencies with regard to knowledge, control and supervision of this activity, both in Rondon do Pará and in the state of Pará. The lack of awareness, control and surveillance points to illegal charcoal production, and the expansion of this activity for settlements and rural settlements of agrarian reform, through the process of monopolization of the territory held by the steel industry, producing pig iron.